THE IMAGE OF CORRUPTED FUTURE EARTH CAUSED BY NATURE EXPLOITATION AS REFLECTED IN AFTER EARTH THE MOVIE - PUTRA, ALFI HAMBRA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: nature exploitation, environment, ecocriticism, After Earth the movie. Nature exploitation threats ecosystem and causes a great damage to environment. The movie entitled After Earth reveals some causes and effects of nature exploitation caused by humans inside the movie. This research applies ecocriticism approach as the main study to analyze After Earth the movie to get the data. This study also applies the concept of movie studies. This research uses verbal data and other nonnumeric data, such as dialogue and scene caption as the basic analysis and in finding solution of the research problems. The result of the study reveals that nature exploitation causes many effects to the environment. In the movie, humans who become the main reason the future earth corrupted because what they did in the past. There are three kinds of nature exploitation found in the movie: excessive factory buildings, deforestation, and excessive animal hunting. The nature exploitations cause such bad effects as the degradation of air quality, flood, and the extinction of animals. Those effects cause imbalance to the cycle of ecosystem which disrupt the life of many living beings.For future researchers, it is advisable to conduct further studies on the same movie but with different approaches. One of the examples is Capitalism combined with Ecocriticism, because Capitalism can be used to analyze the reason why humans exploit natural resources in the movie.